Limit analysis of steel-concrete composite structures with slip = Nośność graniczna zespolonych stalowo-betonowych konstrukcji z poślizgiem - Aliawdin, Piotr; Urbańska, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper proposes a modeling of the load carrying capacity of steel-concrete composite structures with slip. An analytical approach to the load carrying capacity calculation of multilayered composite elements and structures with slip is presented.
Keywords: konstrukcje szkieletowe; konstrukcje zespolone stalowo-betonowe; nośność graniczna; metoda elementów skończonych; optymalizacja; limit analysis; steel-concrete composite structures; beams and bars; slip; FEM; optimization